PERSEPSI AWAL PARA PELAJAR KEJURUTERAAN TEKNOLOGI DI UNIVERSITAS SWASTA TERHADAP AMALAN RASUAH (KORUPSI) DI DALAM KERJAYA - Zin, Mohd Mohamed; Din, Mohd Adri Che; Arifin, Adifarizal Mohd; Ahmad, Noor Kamsiah Che; Ahmad, Norkhairi bin (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
The Integrity and Anti Corruption Course was first implemented at private higher learning institutions in Malaysia in 2022 (UniKL) to follow the National Anti-Corruption Plan (NACP) which aims to realise the vision of the country to be of high integrity and corruption-free. The Integrity and Anti course was made compulsory to be offered and taught as one of the elective courses under the general subject category (MPU). The objective of the study is to measure the level of comprehension of the university students of engineering technology programme on integrity and corruption in Malaysia. This is important for them to be individuals who have high integrity and despise corrupt practices when they join the workforce. This initial study is important to see whether the content, delivery method, and duration of the course are suitable and adequate to create positive impacts among the undergraduates. A total of 89 respondents were chosen as convenient non-probability sampling for this study and all of them have enrolled in the Integrity and Anti-corruption course for 1 semester. They were asked to respond to questions in a survey instrument adapted from previous studies by Malaysia Integrity Institute (MII). The findings from the survey show that the majority of the respondents have a good grasp on what is integrity and why anti-corruption is detrimental to a country. Their general comprehension on the matter of Integrity and Anti-corruption is good but many have the preceptive that some specific examples of corrupt practices are acceptable. This is quite worrisome and the study proposes that this course be further improved and enhanced into a compulsory subject for all university undergraduates. This is to propagate a more comprehensive understanding of integrity and corruption as a crime that must be eradicated.